Impact of Natural Disasters on Household Health and Education Expenditure: Evidence from El Niño Phenomenon in Peru - Malpartida, Raul (2025)
This study examines the impact of the 2017 El Niño phenomenon on per capita expenditures on health and education among rural households in the northern coastal region of Peru. We use household-level panel data from 2015 to 2019, along with district-level precipitation data. A difference-in-differences (DiD) model is proposed to compare households affected by the phenomenon with those that were not affected. The results show that the 2017 El Niño phenomenon had a negative effect on per capita expenditures on health and education for the affected rural households, possibly driven by a negative shock to agricultural income. Consequently, the findings suggest that individuals in affected households have reduced access to the benefits of acquiring health and education services, increasing their vulnerability to health risks and cognitive skill development challenges.